Azimuthal transverse single-spin asymmetries of inclusive jets and identified hadrons within jets from polarized pp collisions at √s = 200 GeV - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2022)
The STAR Collaboration reports measurements of the transverse single-spin asymmetries, AN, for inclusive jets and identified “hadrons within jets” production at midrapidity from transversely polarized pp collisions at √s=200 GeV, based on data recorded in 2012 and 2015. The inclusive jet asymmetry measurements include AN for inclusive jets and AN for jets containing a charged pion carrying a momentum fraction z>0.3 of the jet momentum. The identified hadron within jet asymmetry measurements include the Collins effect for charged pions, kaons, and protons, and the Collins-like effect for charged pions. The measured asymmetries are determined for several distinct kinematic regions characterized by the jet transverse momentum pT and pseudorapidity η, as well as the hadron momentum fraction z and momentum transverse to the jet axis jT. These results probe higher momentum scales (Q2 up to ∼900 GeV2) than current, semi-inclusive deep-inelastic scattering measurements, and they provide new constraints on quark transversity in the proton and enable tests of evolution, universality, and factorization breaking in the transverse-momentum-dependent formalism.
Im Titel steht das s unter dem Wurzelsymbol
Gesehen am 14.11.2023